Snowball Earth Initiation and the Thermodynamics of Sea Ice - Johannes Hörner (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Aiko Voigt (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Christoph Braun (Institute of Meteorology and Climate Research‐Department Troposphere Research, Karlsruhe Institute of Technology (KIT)) (Journal of Advances in Modeling Earth Systems, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1681605 The abstract is available here: https://uscholar.univie.ac.at/o:1681605